Manajemen Pembiayaan Di MTs Bahrul Ulum Krawang Sari Natar Lampung Selatan - Indillah, Muhammad; Yetri, Yetri; Amirudin, Amirudin (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
School financing management is the whole process of trying to obtain and utilize all funds in schools. Seek as many financial sources and sources as possible to obtain funds from financial sources. Based on the results of the survey, the authors were able to identify problems which included: financial planning (budgeting), implementation (accounting) and auditing (auditing) had not been carried out properly. This study uses a qualitative method. Sources of data in this study consisted of the head of the Madrasah, Chair of the Committee, TU, treasurer, Deputy Head of Curriculum, Deputy Head of Student Affairs, teachers. Collecting data in this study using interview techniques, observation and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation and drawing conclusions which were then described descriptively. By implementing financing management through financial management functions, namely financial planning (budgeting), implementation (accounting), inspection (auditing). The implementation of financing management through financial management functions at MTs Bahrul Ulum Krawang Sari Natar has been running as it should. Through this research, the authors recommend that parties related to financial planning (budgeting) be able to increase the number of educational infrastructure in the form of office/study buildings and inventory.